A novel nitronyl nitroxide radical containing thiophene and pyridine rings and its manganese(II) complex: synthesis, structure, and magnetic properties. Issue 11 (3rd June 2017) - Guo, Jian-Ni; Wang, Juan-Juan; Sun, Gui-Fang; Li, Hong-Dao; Li, Li-Cun
Abstract: A novel nitronyl nitroxide NIT-thien-3-Py (2-(3-( m -pyridyl)-2-thienyl)-4, 4, 5, 5-tetramethylimidazoline-1-oxyl-3-oxide) and its Mn(II) complex [Mn(hfac)2 (NIT-thien-3-Py)]2 (hfac = hexafluoroacetylacetonate) have been obtained. X-ray analysis indicates that the Mn(II) complex possesses a cyclic dimer structure in which two radical ligands link two Mn(II) ions through their NO groups and pyridine rings. The study of the magnetic data indicates that the manganese(II) ion strongly and antiferromagnetically interacts with the directly bonding NO group and there is weak ferromagnetic coupling between two Mn–NO pairs through the thiophene and pyridine rings of the radical ligand in agreement with a spin polarization mechanism. Abstract :